Robust identification of non-linear greenhouse model using evolutionary algorithms - Herrero, J.M.; Blasco, X.; Martínez, M.; Ramos, C.; Sanchis, J. (Control engineering practice, 2008)
This paper presents the non-linear modelling, based on first principle equations, for a climatic model of a greenhouse and the estimation of the feasible parameter set ( FPS) when the identification error is bounded simultaneously by several norms. The robust identification problem is transformed into a multimodal optimization problem with an infinite number of global minima that constitute the FPS. For the optimization task, a special evolutionary algorithm ( ε -GA) is presented, which characterizes the FPS by means of a discrete set of models that are well distributed along the FPS. A procedure for determining the norm bounds, such that FPS ≠ ∅ , is presented.